Multi-objective optimal longitudinal flight control system design for a large flexible transport aircraft. - Song, Sipeng (Cranfield University, 2018)
This thesis presents a multi-objective evolutionary algorithm design of a longitudinal optimal controller for a large exible transport aircraft. The algorithm uses a mixed optimization approach based on a combination of Linear Quadratic Regulator(LQR) control and a Multi-Objective Genetic Algorithm (MOGA) to search over a set of possible weighting function structures and parameter values in order to satisfy a number of conflicting design criteria. The proposed approach offers a number of potential optimal solutions lying on or near the Pareto optimal front of competing objectives. The approach is explained in this thesis and some results are presented.
Keywords: Multi-objective optimisation; flexible aircraft; MOGA; LQR; handling quality; algorithm design